PERBEDAAN TINGKAT KESEGARAN JASMANI SISWA SD NEGERI 13 BENGKALIS DENGAN SD NEGERI 05 BENGKALIS - Mawardi Mawardi; Saripin Saripin; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
ABSTRACT. This study originated from the curiosity author of the level of physical fitness of students of SD Negeri 13 with SD Negeri 05 Bengkalis. The purpose of this study was to get a real of how the physical fitness level of each student at the same school and to see the differences in the level of physical fitness of students of SD Negeri 13 with SD Negeri 05 Bengkalis. This type of research is the type of comparative research, the research design "Ex Post Facto". Samples were taken by purposive sampling technique, thus the number of samples is 44 male student. The type of data in the study of primary data derived from the measurement results of the physical fitness of the students were selected to be sampled and secondary data is data obtained from the student's name School of Administration. Then the data were analyzed using data analysis techniques uji-T. The results of data analysis showed that the level of physical fitness of students of SD Negeri 05 better than the physical fitness level of students of SD Negeri 13 Bengkalis, obtained from the study of physical fitness with a mean SD Negeri 05 The average (mean) is 16.85, the standard deviation is 3.15, the highest score of 22 and the lowest score of 10, a distance measurement (range) is 12, while SD Negeri 13 Bengkalis with arithmetic mean (the mean) is 14.71, the standard deviation was 2.87, the highest score was 19 and the lowest score is 10, a distance measurement (range) is 9. The results of the analysis of the coefficients obtained t = 3.19 and table = 1.68.Keywords : differences in the level of physical fitness